VREnergy: A simulator for critical operating procedures in electrical substations with evaluation process - Ribeiro, Saulo P.; Martins, Thiago Silva; Meynard, Gabriel Alejandro; Costa, Lucas Bertolino Santos; Santos, Gabriel de O. M.; Melotti, André Coco Pereira; Carvalho, Gabriel Cordeiro de; Lopes, Matheus Muruci de S. (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2024)
This article presents a VR simulator developed with Unity 3D for critical electrical maintenance procedures in a factory setting. The simulator offers two modes: tutorial, for guided step-by-step instruction, and free mode, for independent skill testing. Upon completion, operators receive detailed performance reports with scores based on their procedural errors. The simulator has proven effective in reducing factory accidents and increasing operator engagement in training sessions.